Pemetaan Tren Riset dalam Manajemen Pendidikan: Studi Bibliometrik dengan VOSviewer (2019-2023) - Mulyanto, Agus; Wardani, Dani; P. Yogaswara, Sunsun; Rukhaida, Ida (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
Many researchers, including academics and practitioners, have conducted studies on the topic of educational management. From the many research results on the theme of education management, there needs to be mapping to make it easier for other researchers to see the distribution of research results on education management. It is crucial to map the results of research on education management so that what has been researched can be known and duplication in research can be avoided. This study aims to see research trends related to education management in the Scopus database. The approach in this study uses quantitative (statistical) with the Bibliometric Analysis method. Bibliometric analysis is divided into four stages, namely first determining the purpose and scope of the study, second using science mapping analysis techniques related to education management, collecting data taken from the Scopus database by entering the keyword "education management" from the 2019-2023 time frame. In addition, the search is limited to using document types in the form of articles, source types in the form of journals and source languages used in English. The four data collection results were mapped based on the number of publications per year, then using the VOSviewer application to see collaboration trends and country networks, citations, research focus and research keywords as well as new themes in the field of education management from 2019-2023. The results showed that the trend of publications related to education management has increased in recent years, although in 2020, it decreased. China and Indonesia are two countries that have significant influence in this field. The research focuses on education management, including 1) human, humans, and education; 2) information management, big data, and colleges and universities; 3) decision-making, higher education, and management information; 4) data mining, management systems, and high educations, and 5) education management, students, and education computing. The new themes in this field are association rules, data technologies and student education. The five research focuses, and contemporary themes in this field can be a reference for future research that wants to explore education management in order to determine the specific area to be researched.